2016
DOI: 10.1126/science.aaf6803
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 mediates axonal degeneration by promoting inflammation and necroptosis in ALS

Abstract: Mutations in Optineurin (Optn) gene have been implicated in both familial and sporadic amyotrophic lateral sclerosis (ALS). However, the role of this protein in the central nervous system (CNS) and how it may contribute to ALS pathology is unclear. Here, we found that optineurin actively suppressed RIPK1-dependent signaling by regulating its turnover. Loss-of-OPTN led to progressive dysmyelination and axonal degeneration through engagement of necroptotic machinery, including RIPK1, RIPK3 and MLKL, in the CNS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
555
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(595 citation statements)
references
References 40 publications
29
555
9
2
Order By: Relevance
“…Astrocytes release TNF-α, FasL, and TRAIL, which can trigger necroptosis through RIPK1 and MLKL activation, and this mechanism has been demonstrated in murine models of ALS (6). RIPK1-mediated axonal pathology was observed in pathological specimens from ALS patients (7). Necroptotic mechanisms were also observed in MS pathological samples (8).…”
Section: Mechanisms Of Neurodegenerationmentioning
confidence: 82%
“…Astrocytes release TNF-α, FasL, and TRAIL, which can trigger necroptosis through RIPK1 and MLKL activation, and this mechanism has been demonstrated in murine models of ALS (6). RIPK1-mediated axonal pathology was observed in pathological specimens from ALS patients (7). Necroptotic mechanisms were also observed in MS pathological samples (8).…”
Section: Mechanisms Of Neurodegenerationmentioning
confidence: 82%
“…In iWAT, seven of the 61 cytokines/chemokines showed a significant change in their expression with age and DR altered the expression of only three cytokines/chemokines (Figure 2b, right panel and Table S1). The data in Figure 2c show that the transcript levels of the pro‐inflammatory cytokines IL‐6, TNF‐α, and IL‐1β, which are strong predictors of mortality and chronic diseases in elderly humans (Singh & Newman, 2011) and have been shown to be induced by necroptosis (Ito et al., 2016), are significantly increased in eWAT from old mice 3.9‐, 4.7‐, and 5.1‐fold, respectively, and are attenuated by DR.…”
mentioning
confidence: 92%
“…Phosphorylated MLKL (P‐MLKL) oligomerizes, binds to, and ruptures the cell membrane, resulting in the release of cellular components including DAMPs. Several studies show that blocking necroptosis either genetically or pharmacologically dramatically reduces inflammation in a variety of mouse models (Ito et al., 2016; Meng et al, 2015). In addition, blocking/reducing necroptosis appears to have an impact on the aging of the male reproductive system (Li et al., 2017) and increases the lifespan of ApoE knockout mice (Meng et al., 2015) and G93A transgenic mouse model of ALS (Ito et al., 2016).…”
mentioning
confidence: 99%
“…Recently, Re et al [32] and Ito et al [34] found that necroptosis may be involved in the MN death. This finding provides an important connection between neurodegeneration and previously observed abnormal inflammation/immune response in ALS.…”
Section: Necroptosis and Immune Dysfunctionmentioning
confidence: 99%
“…Recently, Cirulli et al [33] compared the whole exome sequences between ALS and control, and found that the non-canonical IκB kinase family TANK-binding kinase 1 (TBK1) was a gene associated with ALS by interacting with ALS-related proteins, optineurin (OPTN) and p62. Furthermore, Ito et al [34] demonstrated that OPTN inhibited dysmyelination and axonal degeneration through suppressing receptorinteracting kinase 1 (RIPK1) and the downstream subsets are preferentially elicited in ALS has been elusive. Recently, several studies support that the programmed necrosis (necroptosis), a new type of cell death, is present in ALS.…”
Section: Necroptosis and Its Implications In Alsmentioning
confidence: 99%